2017
DOI: 10.1016/j.cub.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and Morphology of Extinct Paleognaths Reveal the Origin and Evolution of the Ratites

Abstract: The Palaeognathae comprise the flightless ratites and the volant tinamous, and together with the Neognathae constitute the extant members of class Aves. It is commonly believed that Palaeognathae originated in Gondwana since most of the living species are found in the Southern Hemisphere [1-3]. However, this hypothesis has been questioned because the fossil paleognaths are mostly from the Northern Hemisphere in their earliest time (Paleocene) and possessed many putative ancestral characters [4]. Uncertainties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
229
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(252 citation statements)
references
References 35 publications
20
229
3
Order By: Relevance
“…Extinction of the original vagile ancestor lineages over time may then result in the appearance of dispersal-limited groups with relict distributions. This cycle of range expansion, morphological evolution and extinction has recently been favoured to explain the distributions of non-vagile birds as diverse as the flightless ratites and tinamous [5,7,8], and the mostly flightless New Zealand wrens [16]. However, in these cases, the putative vagile ancestors were purely hypothetical.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extinction of the original vagile ancestor lineages over time may then result in the appearance of dispersal-limited groups with relict distributions. This cycle of range expansion, morphological evolution and extinction has recently been favoured to explain the distributions of non-vagile birds as diverse as the flightless ratites and tinamous [5,7,8], and the mostly flightless New Zealand wrens [16]. However, in these cases, the putative vagile ancestors were purely hypothetical.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these cases, the putative vagile ancestors were purely hypothetical. The only fossil evidence of vagile ratites is from the Palaearctic, where no extant ratites reside [8,[17][18][19]. Similarly, all known fossil New Zealand wrens already feature non-vagile traits [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the correlations between continental drift and phylogenetic branching patterns of terrestrial animals such as Eutherian mammals (Nishihara et al, 2009;dos Reis et al, 2012), Palaeognathae (ratite and tinamou: Cooper et al, 2001;Haddrath and Baker, 2012;Yonezawa et al, 2017), Pleurodira (side-necked turtle: Vargas-Ramírez et al, 2008), Anura (frogs: Bossuyt et al, 2006), Cichlidae (cichlid fish: Friedman et al, 2013) and Plecoptera (stoneflies: McCulloch et al, 2016) have been vigorously argued. Some of these studies (e.g., Haddrath and Baker, 2012;dos Reis et al, 2012;Yonezawa et al, 2017) suggested that biogeographical distribution patterns were not necessarily established merely by continental drift, but that the overseas 'sweepstakes dispersal route' (Simpson, 1940) should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies (e.g., Haddrath and Baker, 2012;dos Reis et al, 2012;Yonezawa et al, 2017) suggested that biogeographical distribution patterns were not necessarily established merely by continental drift, but that the overseas 'sweepstakes dispersal route' (Simpson, 1940) should be considered. A sweepstakes dispersal route is "a possible route of faunal interchange which is unlikely to be used by most animals, but which will, by chance, be used by some" (Allaby, 1999).…”
Section: Introductionmentioning
confidence: 99%